An exploratory study on violence among the college students in Urban Bengaluru, Karnataka, India - N R Ramesh Masthi; A R Manasa (Wolters Kluwer Medknow Publications, 2019)
Violence often blights people's lives for decades, leading to drug addiction, depression, suicide, school dropout, unemployment, and recurrent relationship difficulties. This exploratory study was conducted among professional degree colleges in urban Bengaluru from January to March 2017; the objectives were to find the magnitude, forms, and substance use in violence. A total of 450 students were studied. One hundred and twenty-three (27.3%) students experienced some kind of violence in the past 1 year and 77 (62.6%) were males. Verbal abuse (65.0%), pushing around (23.6%), and slapping (18.7%) were common forms of violence observed. Substance use was significantly associated with violence.